Analysis of Table Tennis Forehand and Backhand Learning Results: Independent Learning Curriculum with A Scientific Approach - Mappaompo, Adam; Aprilio, Ians; Said, Poppy (Journal of Physical and Outdoor Education, 2023)
This study aims to determine the learning outcomes of forehand and backhand strokes in table tennis using a scientific approach in class VIII students of SMP Negeri 2 Ulaweng. The variables in this study were the learning outcomes of forehand strokes and the learning outcomes of backhand strokes in table tennis games. The population in this study were all class VIII students of SMP Negeri 2 Ulaweng, totaling 127 students consisting of 59 male students and 68 female students. The research sample was 31 students of class VIII SMP Negeri 2 Ulaweng. Data collection techniques in this study used observation sheets. The data analysis technique used was descriptive statistics using the SPSS version 20 program. The results obtained were 10 students in the good category with a percentage of 32%, 21 students in the very good category with a percentage of 68%. So it can be concluded that the learning outcomes of forehand and backhand strokes in table tennis using a scientific approach in class VIII students of SMP Negeri 2 Ulaweng are in the very good category with a percentage of 68%.